Bayside Liquid Soap; Pollard & Leighton, Military Goods; Hope & Whitney, Signs; McLaughlin Brush Manufactory, Murphy, Leavens, & Co. - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Bayside Liquid Soap; Pollard & Leighton, Military Goods; Hope & Whitney, Signs; McLaughlin Brush Manufactory, Murphy, Leavens, & Co. from the 1870 Boston City Directory